Hubungan Dukungan Suami Terhadap Partisipasi Ibu Mengikuti Kelas Ibu Hamil Di Wilayah Kerja Puskesmas Wiradesa Kabupaten Pekalongan - Dhina Mahfira; Remilda Armika Vianti; Anik Indriono (PENA NURSING, 2023)
Background. Pregnant Women Class is an activity that pregnant women participate in to get information about pregnancy with 10 participants. The purpose of this activity is to increase knowledge, change behavior and attitudes about pregnancy, pregnancy care, childbirth, postpartum, family planning, newborn care.Purpose. Knowing the relationship of husband's support to mother's participation in classes for pregnant women in the working area of the Wiradesa Community Health Center.Method. The method used in this study is a quantitative research method with a cross sectional approach. The sample used in this study was 20 respondents using the Chi Square statistical testResults. The results of the study after the Kendal's Tau test got a p-value of 0.855 so that the p-value > 0.05. Based on statistical tests, it can be found that there is no significant relationship between the relationship of husband's support to the participation of mothers in attending classes for pregnant women in the working area of the Wiradesa Public Health Center, Pekalongan Regency.Conclusion. There is no relationship between husband's support for mother's participation in classes for pregnant women in the work area of the Wiradesa Public Health Center, Pekalongan Regency.